2006
DOI: 10.1167/iovs.05-1442
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Classification of Parvalbumin-Containing Retinal Ganglion Cells in Mouse: Single-Cell Injection after Immunocytochemistry

Abstract: Single-cell injection, after immunocytochemistry, provided the first means to identify the detailed functional anatomy of parvalbumin-containing RGCs in the mouse retina. The combined approach of cell morphology and the selective expression of parvalbumin will not only provide useful data for further correlation of physiological properties of the RGCs, but it will also provide a useful strategy for matching a neuron's morphology with its expression of a particular protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 43 publications
14
52
0
Order By: Relevance
“…Parvalbumin is a Ca 2+ buffer protein, which is highly expressed in the vast majority of GABAergic neurons (Celio, 1986(Celio, , 1990) of the visual thalamocortical circuit and in the retina (Kim and Jeon, 2006). With respect to the visual pathway it is also of interest that PV has been reported to play an important role in the superior colliculus (Lane et al, 1997;Kang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parvalbumin is a Ca 2+ buffer protein, which is highly expressed in the vast majority of GABAergic neurons (Celio, 1986(Celio, , 1990) of the visual thalamocortical circuit and in the retina (Kim and Jeon, 2006). With respect to the visual pathway it is also of interest that PV has been reported to play an important role in the superior colliculus (Lane et al, 1997;Kang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Parvalbumin is highly expressed in GABAergic neurons (Celio, 1990) and the reactivity for the perineuronal net marker around GABAergic neurons confirmed that GABAergic neurons are still viable in PVKO mice (Schwaller et al, 2004). Specific parvalbumin immunoreactivity (PV-ir) was identified within subpopulations of ganglion and amacrine cells of the mouse retina (Endo et al, 1986;Sanna et al, 1993;Kim and Jeon, 2006). However, the study of the functional properties of the visual pathway of mice has attracted limited attention by the neurophysiologists in the past probably because of the poor visual acuity of this species (Prusky et al, 2000).…”
Section: Introductionmentioning
confidence: 87%
“…8 GCs and ACs may both reside in the GC layer (GCL) and inner nuclear layer (INL), and they are not obviously distinguishable by soma size, 15,16 axons, 17,18 or dendritic tree shape. 6,15,19 Amacrine cells are often identified immunologically by antibodies against GABA, glycine, 20,21 Choline acetyltransferase (ChAT), 20,22 tyrosine hydroxylase (TH), [23][24][25] and neuronal or brain-type nitric oxide synthase (nNOS or bNOS), [26][27][28] while antibodies against calcium-binding proteins, such as parvalbumin (PV) [29][30][31] and calretinin (CR), 32-34 may label GCs. A more reliable way to distinguish GCs from ACs, however, is retrograde labeling of GCs.…”
mentioning
confidence: 99%
“…[35][36][37] In the retrogradely labeled mouse retina, the specificity of GABA, glycine, ChAT, and nNOS antibodies in labeling retinal ACs has been recently confirmed, 28 but similar investigations have not been done for TH, 38 CR, [32][33][34] and PV. [29][30][31] Of the multiple subtypes of ACs, GABA ACs are the only subtype that have been confirmed to couple with GCs. 39,40 It is still unknown how many GABA ACs and other subtypes of ACs are coupled with GCs and whether all the cells in an individual immunological subpopulation contact the same number and types of GCs or ACs.…”
mentioning
confidence: 99%
“…Some of the cells had multiple axons and a fat cell body resembling authentic RGCs ( fig. 1 F) [30] . The pax6 -transfected cells did not extend axon-like processes without the addition of fibronectin to culture medium ( fig.…”
Section: Induction Of Cloned Pax6-transfected Cellsmentioning
confidence: 98%